2014
DOI: 10.3390/ma7117339
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Mechanisms in Resistance Switching Memory Devices Using Transparent Boron Doped Zinc Oxide Films

Abstract: In this work, metal/oxide/metal capacitors were fabricated and investigated using transparent boron doped zinc oxide (ZnO:B) films for resistance switching memory applications. The optical band gap of ZnO:B films was determined to be about 3.26 eV and the average value of transmittance of ZnO:B films was about 91% in the visible light region. Experimental results indicated that the resistance switching in the W/ZnO:B/W structure is nonpolar. The resistance ratio of high resistance state (HRS) to low resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…It is reported that for Φ T >> Φ ξ , the hopping conduction current increases with increasing temperature ( Figure S5c, Supporting Information). [25] Following the same trend, the hopping conduction current increases in sub-quantum CBRAM devices, as shown in Figure 5d. The estimated activation energy is ≈ 310 meV, further confirms the deeper labels of defect sites.…”
Section: Wwwadvelectronicmatdesupporting
confidence: 64%
See 1 more Smart Citation
“…It is reported that for Φ T >> Φ ξ , the hopping conduction current increases with increasing temperature ( Figure S5c, Supporting Information). [25] Following the same trend, the hopping conduction current increases in sub-quantum CBRAM devices, as shown in Figure 5d. The estimated activation energy is ≈ 310 meV, further confirms the deeper labels of defect sites.…”
Section: Wwwadvelectronicmatdesupporting
confidence: 64%
“…reported that hopping conduction is the dominating mechanism for an electric field over 0.2 MV cm −1 . [ 25 ] If J is the current density, ξ is the electric field, q is the electronic charge, δ is the hopping distance between nearest neighbors or trap spacing, η is the e’ concentration in conduction band, γ is the vibration frequency, T is the absolute temperature, k is the Boltzmann's constant, Φ T is the trap energy level, then the hopping conduction can be expressed as J=qδηγ×exp[]qδξkTΦTkT …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, controlled deposition parameter and post-thermal treatment on resistive layer may be not as effective as doping technique to fully adjust the defect concentration. Various dopant elements, such as Al [ 137 , 175 , 176 ], B [ 177 ], Co [ 138 , 139 , 169 , 178 ], Cr [ 110 , 158 ], Cu [ 87 , 140 , 179 ], Fe [ 180 , 181 ], Ga [ 112 , 182 , 183 ], La [ 144 ], Li [ 184 , 185 ], Mg [ 55 , 111 , 145 , 186 190 ], Mn [ 91 , 146 148 , 191 – 195 ], N [ 56 , 149 ], Ni [ 196 ], S [ 197 ], Sn [ 90 , 198 ], Ta [ 199 ], Ti [ 150 , 151 ], V [ 85 ], and Zr [ 86 ], that have been reported may exhibit decent switching performance. ZnO-based RRAM with multi-element doping, such as Al-Sn [ 136 , 200 ], Ga-Sn [ 201 ], and In-Ga [ 141 143 , 202 – 208 ], is also proposed.…”
Section: Reviewmentioning
confidence: 99%
“…Employing an amorphous resistive layer may also avoid the formation of excessive and branching of CF due to the lack of grain boundary structure. Several efforts have been reported to fabricate amorphous ZnO-based RRAM, such as by doping [ 90 , 141 143 , 177 , 198 , 201 203 , 205 208 ], hydrogen peroxide treatment [ 183 ], and deposition parameter optimization [ 132 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, ZnO-based diluted magnetic semiconductors showed ferromagnetism in ZnO by doping with boron or a transition metal, which is promising to achieve practical Curie temperature for future spintronic devices [ 3 , 4 ]. In addition, transparent boron-doped ZnO (ZnO:B) films sandwiched between two tungsten electrodes showed memristive behavior, which is attractive to overcome the physical limitations of traditional Flash memory for the next generation nonvolatile memory applications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%